Efficacy and safety of cerebral embolic protection systems during transcatheter aortic valve replacement: a review of current clinical findings. (3rd August 2021) - Sato, Yu; Kawakami, Rika; Sakamoto, Atsushi; Cornelissen, Anne; Mori, Masayuki; Kawai, Kenji; Ghosh, Saikat; Romero, Maria E.; Kolodgie, Frank D.; Virmani, Renu; Finn, Aloke V.
ABSTRACT: Introduction: Cerebrovascular events are one of the most serious consequences after transcatheter aortic valve replacement (TAVR). More than half of the cerebrovascular events following TAVR are due to procedure-related emboli. Embolic protection devices (EPDs) have the potential to decrease cerebrovascular events during TAVR procedure. However, randomized controlled trials (RCTs) have not conclusively determined if EPDs are effective, likely because of small number of patients enrolled. However, meta-analyses and propensity-matched analyses from large registries have shown efficacy and suggest the importance of EPDs in prevention of stroke during TAVR and perhaps other structural heart procedures. Areas covered: This review will focus on clinical and histopathologic studies examining the efficacy, safety, and histopathologic device capture findings in the presence and absence of EPDs during TAVR procedures. Expert opinion: Clinical studies have not conclusively determined the efficacy of EPDs. Current ongoing large-scale RCT (PROTECTED TAVR [NCT04149535]) has the potential to prove their efficacy. Histopathological evaluation of debris captured by EPDs contributes to our understanding of the mechanisms of TAVR procedure-related embolic events and suggests the importance of preventing cerebral embolization of debris released during this and other structural heart procedures.